The Repertory Grid in Career Counselling: Role and Value - Cochran, Larry R. (Canadian Journal of Counselling and Psychotherapy, 2012)
The potential role of Kelly's (1955) repertory grid in career counselling is discussed. Its value in helping students make career decisions, establish bases for future development and learn how to make decisions in general is clarified.